RETRACTION: Fan X, Tanomtong A, Chaveerach A, Pinthong K, Pornnarong S, Supiwong W, Liehr T, Weise A. High Resolution Karyotype of Thai Crab-Eating Macaque (Macaca fascicularis). Arch Biol Sci. 2014;66(4):1603-7. - team, Editorial (Archives of Biological Sciences, 2022)
This is a notice of retraction of the article: High resolution karyotype of Thai crab-eating macaque (Macaca fascicularis) by Xiaobo Fan, Alongkoad Tanomtong, Arunrat Chaveerach, Krit Pinthong, Siripiyasing Pornnarong, Weerayuth Supiwong, Thomas Liehr, and Anja Weise, published in: Archives of Biological Sciences in 2014, Vol. 66, Issue 4: https://doi.org/10.2298/ABS1404603F. The Editor-in-Chief has been informed that this paper is a duplicate of the paper: High resolution karyotype of Thai crab-eating macaque (Macaca fascicularis) by Xiaobo Fan, Alongkoad Tanomtong, Arunrat Chaveerach, Krit Pinthong, Siripiyasing Pornnarong, Weerayuth Supiwong, Thomas Liehr, Anja Weise, published in: Genetika, Vol. 46, No. 3, 877-882, 2014: https://doi.org/10.2298/GENSR1403877F This claim is correct and the entire paper is a verbatim copy of the earlier one. After confirmation of this fact, the Editor-in-Chief of the Archives of Biological Sciences has decided to retract the paper immediately. We apologize to the readers of the journal that it took so many years to notice this error and to retract the paper. We request readers of the journal to directly get in touch with the editorial office and the editors of the journal for similar cases in the future so that they can be handled promptly.